STRATEGI NEGOSIASI PEMERINTAH KOTA MADIUN DALAM PROSES RELOKASI PEDAGANG KAKI LIMA - Nurhana Marantika; Muhammad Daekan Wahyuda; Umbu TW Pariangu (Journal Publicuho, 2024)
This study was conducted to determine the negotiation strategy of the Madiun City government in the process of relocating street vendors. The government also uses good methods in this relocation process so that the relocation process can run well. This type of qualitative descriptive research uses data analysis techniques by conducting interviews, observations, and documentation by identifying, assessing, and understanding how the form of negotiations carried out by the Madiun city government in the process of relocating street vendors on Jl Dr Soetomo to Jl Rimba Dharma. The results of this study show that the negotiation strategy used by the Madiun City Government is a Win-win Strategy. In this case, the street vendors get benefits, namely: in preparing a place before the relocation process, the government has facilitated a place for street vendors by not charging a penny and making Rimba Dharma one of the culinary centres in Madiun. The benefits obtained by the Government, namely: traffic becomes smooth, flattens the city crowd, the city, and the economy in the city of Madiun.